BENTUK BUMI BULAT ATAU DATAR:: SEBUAH STUDI TEOLOGI ALKITAB TERHADAP BENTUK BUMI - Sulistiono (STT-RAI Batam, 2025)
The debate over the shape of the Earth, whether spherical or flat, has remained a subject of continuous discussion in many fields, including theology. This study seeks to analyze the biblical portrayal of the Earth's shape in Old Testament writings, particularly through a hermeneutical approach combining historical-critical analysis and semantic study of key Hebrew terms such as ḥug and raqia. The research adopts a qualitative method grounded in literature review, using the Bible as the primary source and supplemented by references from biblical theology and ancient cosmology. The findings indicate that Old Testament cosmology consistently portrays the Earth as a fixed entity surrounded by a dome-shaped firmament, with the separation of waters above and below. These results suggest that, within the cultural and faith context of ancient Israel, the flat-earth model served as the conceptual framework shaping theological understandings of creation. This research is expected to enrich theological and hermeneutical discourse on biblical cosmology while offering a fresh perspective for dialogue between faith and science.